Perceptions of COVID-19 Online Learning Students Based on Dreem in Class 2020 Students of the Faculty of Medicine Universitas Airlangga, Surabaya, Indonesia - Mirza Nur Mazidah; Hasan, Helmia; Utomo, Budi (Journal of Community Medicine and Public Health Research, 2024)
A learning environment is anything that can influence changes in attitudes in teaching and learning activities which will further influence the achievement of learning outcomes and student development. A researcher wants to carry out research on student perceptions regarding changes in the online learning environment due to Coronavirus Disease 19 (COVID-19) in the Faculty of Medicine, Universitas Airlangga. The study aimed to describe the perceptions of the students toward five aspects of an online learning environment. This study was a descriptive research using a quantitive approach and the sampling technique used simple random sampling with 167 medical faculty student class 2020. One hundred sixty-seven respondents' data were collected using the specific measurement tool Dundee Ready Education Environment Measure (DREEM) to measure the learning environment with univariate analysis. The results obtained from this research showed that the perception of students at the Faculty of Medicine, Universitas Airlangga towards the online learning environment is quite good with a score of 139.48. The result of this study indicated that the mean DREEM score was 139.48/200 (SD 22.76) is in the good category. Although the learning environment is in a good category, several points need to be improved so the faculty can increase the quality of the medical education.